PRAKTIKALITAS LEMBAR KERJA MAHASISWA BERBASIS KPS TERHADAP HASIL BELAJAR KOGNITIF MAHASISWA - Sari Indriyani; Ita, Ita (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
This research is a development research to develop student worksheets. The aim of this study is develop LKM based on KPS in virus and bactery concept toward the cognitive learning outcomes and find out the practicality level. This development research refers to the 4D development model which includes the stages of define, design, develop. Instruments for data collection were questionnaire sheets and essay questions. The analysis was carried out based on the practicality questionnaire of LKM and the score of students' cognitive learning outcomes. The results of this development research indicate that LKM is considered practical by students in terms of attractiveness, usage and time. In addition, the developed LKM can improve students' cognitive skills with grades above the graduation average